2017
DOI: 10.1038/ncomms14228
|View full text |Cite
|
Sign up to set email alerts
|

Dub3 inhibition suppresses breast cancer invasion and metastasis by promoting Snail1 degradation

Abstract: Snail1, a key transcription factor of epithelial–mesenchymal transition (EMT), is subjected to ubiquitination and degradation, but the mechanism by which Snail1 is stabilized in tumours remains unclear. We identify Dub3 as a bona fide Snail1 deubiquitinase, which interacts with and stabilizes Snail1. Dub3 is overexpressed in breast cancer; knockdown of Dub3 resulted in Snail1 destabilization, suppressed EMT and decreased tumour cell migration, invasion, and metastasis. These effects are rescued by ectopic Snai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
109
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 65 publications
3
109
0
Order By: Relevance
“…Expression of Dub3 blocked Snail degradation mediated by the E3 ligases Fbxl14 and Fbxw1/β-TRCP1 [38] . Functionally, we found that the expression of Dub3 in breast cancer cell lines not only downregulates markers of luminal type of breast cancer, but also upregulates molecules associated with BLBC [38] . Knockdown of Dub3 inhibits migration, invasion and cancer stem cell (CSC)-like characteristics in cells by downregulating of Snail.…”
Section: The Deubiquitination Of Snailmentioning
confidence: 99%
See 4 more Smart Citations
“…Expression of Dub3 blocked Snail degradation mediated by the E3 ligases Fbxl14 and Fbxw1/β-TRCP1 [38] . Functionally, we found that the expression of Dub3 in breast cancer cell lines not only downregulates markers of luminal type of breast cancer, but also upregulates molecules associated with BLBC [38] . Knockdown of Dub3 inhibits migration, invasion and cancer stem cell (CSC)-like characteristics in cells by downregulating of Snail.…”
Section: The Deubiquitination Of Snailmentioning
confidence: 99%
“…IL-6 is also identified as a major cytokine secreted by BLBC cells and is essential for the CSC-like characteristic of BLBC [41] . Interestingly, Dub3 activity and expression, at both the mRNA and protein levels, can be induced by IL-6 through the JAK/STAT3 signaling pathway [31,38,39] . Consistent with this, we also found that IL-6 rapidly induces Dub3 expression, exerting a maximum effect at 2hr [38] .…”
Section: The Deubiquitination Of Snailmentioning
confidence: 99%
See 3 more Smart Citations